Carbothioamide as Highly Efficient Ligand for Copper‐catalyzed Room Temperature Chan–Lam Cross‐Coupling Reaction. (26th September 2017) - Baruah, Jayantajit; Gogoi, Kongkona; Dewan, Anindita; Borah, Geetika; Bora, Utpal
Abstract : The catalytic activity of three N, S‐donor ligands, viz L1 [2‐(4‐methoxybenzylidene)‐ N ‐phenylhydrazinecarbothioamide], L2 [2, 2′‐(1, 2‐diphenylethane‐1, 2‐diylidene)bis(hydrazinecarbothioamide)] and L3 [2‐(4‐methoxybenzylidene)hydrazinecarbothioamide] has been reported for N‐arylation of imidazoles with arylboronic acids in ethanol at room temperature. The method was found to be applicable in N‐arylation for a wide range of electronically diverse arylboronic acids with imidazoles having modest to excellent isolated yields. The in situ generated copper(II) complex of the ligand namely, 2‐(4‐methoxybenzylidene)‐ N ‐phenylhydrazinecarbothioamide (L1) was found to be highly efficient homogeneous catalyst for N‐arylation reaction. Abstract :